Local Community Life Satisfaction at Early Stage Tourist Destination - Abdillah, Fitri; Leewellyn, Vincent; Yadisaputra, Michael (E-Journal of Tourism, 2020)
The developing destinations are marked by increasing level of community life satisfaction. The objective of study is to identify the level of life satisfaction of local people in early stage tourist destinations. The method is a survey with a mix method analysis to justify the findings. Primary data were obtained from 6 tourism actors and local community leaders, while secondary data were obtained from official government institutions. The location of the study was two mangrove destination in North Karawang, West Java. The results showed that in the early stages of tourism destination development, the level of life satisfaction of the local community showed a high response to the subjective indicators but lower to the objective. In subjective indicators, the highest response occurs in the community's collectivity in building, but low in fulfilling personal aspects, especially awareness about the future. Local people feel relatively satisfied with their living conditions, especially family, social religious situation, and physical environment. They also view that tourism can be an alternative way out to improve economic conditions and the physical environment. Further research needs to see behavioral changes of local community to face destination development due to the increasing number of tourists. Keywords: early stage destination, life satisfaction, community